ANALISIS PERBANDINGAN KETELITIAN PENGUKURAN KERANGKA KONTROL HORISONTAL ORDE â€“ 4 DENGAN GPS LOWCOST - Redy Maulana; Mokhamad Nur Cahyadi (Kokoh, 2023)
A point positioning activity can be referred to as mapping. In mapping activities there is the term control framework point. One of the classification of control points is the horizontal control point. In mapping activities there is a minimum order of control points that can be used, that was horizontal control points order-4. The measurement of horizontal control points order-4 can be done by conventional survey methods using terrestrial method or using global positioning system technology. The development of global positioning system (GPS) technology has progressed very fast. One of the evidence of the development of GPS technology is where introduced of various instruments that exist today. Lowcost GPS is one type of GPS that has advantages in terms of more lower prices. The application of lowcost gps is expected to help in mapping activities. In this reserch, a feasibility analysis of lowcost GPS OEM Board K-708 and GPS Tersus BX-316as instruments in the measurement of horizontal control frame order-4 when compared with Geodetic GPS instruments. The analysis used in this study is standard deviation analysis and hypothesis testing using T-test. From the results of analysis conducted resulted in the accuracy of the instrument shown from the value of standard deviation that reached sub "cm", where the instrument GPS OEM Board K-708 has better standard deviation than GPS Tersus BX-316. From the results of hypothesis testing using T-Test showed no significant difference from each of the data, so it can be concluded that the instruments in this reserch are worthy of the use in the measurement of horizontal control framework order-4.Â Keywords: GPS Lowcost, Jaring Kontrol Horizontal Orde-4, Standar Deviasi, Uji-T